2009
DOI: 10.2320/jinstmet.73.878
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Aluminum Alloy 6063 in Gasoline with Ethanol

Abstract: Behavior of dry corrosion which is electrochemical reaction between Al Mg Si alloy 6063 and ethanol in gasoline has been investigated. Dry corrosion has not been observed in E3 (3 ethanol) and E10 (10 ethanol) at room temperature, but observed in E3 and E10 when a small amount of aluminum chloride had been added to them at room temperature. The higher solution temperature is, the more often the dry corrosion occurs. Dry corrosion has also been observed in the above solution environments in which 0.1 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Oxidation of the grooves and ridges on the Al disk could be caused by ethanol and/or dissolved oxygen during sliding. Al has been reported to react with both dissolved oxygen and ethanol in liquid ethanol [20,21] . It has been reported that thermal melting and softening of the PE surface is caused by frictional heat when PE is slid against smooth metal under dry conditions [5,6].…”
Section: Observation and Chemical Analysis Of Worn Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation of the grooves and ridges on the Al disk could be caused by ethanol and/or dissolved oxygen during sliding. Al has been reported to react with both dissolved oxygen and ethanol in liquid ethanol [20,21] . It has been reported that thermal melting and softening of the PE surface is caused by frictional heat when PE is slid against smooth metal under dry conditions [5,6].…”
Section: Observation and Chemical Analysis Of Worn Surfacesmentioning
confidence: 99%
“…n-Undecane hardly reacted with Al and Ti because the reactivity of hydrocarbon is low [29]. However, ethanol reacted with Al and Ti to form the metal ethoxides Al(OC 2 H 5 ) 3 and Ti(OC 2 H 5 ) 4 , respectively [20,21,25]. Metal oxide and metal hydroxide were formed by the hydrolysis and dehydrative condensation reactions of metal ethoxide via a metaloxane polymer [-(M-O) n -] [22,23,26].…”
Section: Chemical Reactivity Of Organic Solvent To Metalmentioning
confidence: 99%
“…(3)] is very fast [5,21]. Aluminum ethoxide [Al(OC 2 H 5 ) 3 ] is hydrolyzed by water, which is an impurity in the ethanol, to form polyaluminoxane gel [-(Al-O) n -] [1,24].…”
Section: Sintered Al-si Disk/stainless Steel Pin Pairmentioning
confidence: 99%